1998
DOI: 10.1097/00005537-199802000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Results of Functional Endoscopic Sinus Surgery

Abstract: Although much has been reported on the short-term outcomes of functional endoscopic sinus surgery (FESS), little has been reported with regard to its long-term impact on chronic sinusitis. The senior author (D.W.K.) previously reported detailed subjective and endoscopic follow-up on 120 patients at a mean of 18 months following surgery. This current study represents a long-term follow-up (average, 7.8 years) of 72 patients (60%) from the same cohort. Of patients responding to a question about overall symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
376
4
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(417 citation statements)
references
References 12 publications
25
376
4
12
Order By: Relevance
“…8 From the literature, it appears that nasal endoscopy provides more important objective evidence of CRS and corroborates findings with polyps grades in the majority of patients. 6,9,10 In some cases, infections also found with harvesting of inflammatory mediators or eosinophils. 8 The radiographical diagnosis may not ne indicated in this study, thus it could probably be considered when the symptoms persist in spite of medical therapy or when a surgical intervention is needed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 From the literature, it appears that nasal endoscopy provides more important objective evidence of CRS and corroborates findings with polyps grades in the majority of patients. 6,9,10 In some cases, infections also found with harvesting of inflammatory mediators or eosinophils. 8 The radiographical diagnosis may not ne indicated in this study, thus it could probably be considered when the symptoms persist in spite of medical therapy or when a surgical intervention is needed.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of continuous suction at the operative site is a technical limitation that compounds the stress for the surgeon and increases the inherent risk for the patient. 3,6 Int J Med Res Prof.2016; 2(5); 93-96.…”
Section: Introductionmentioning
confidence: 99%
“…Senior et al [12] reported improvement in headache in 47 of 51 patients at 7.8-year after ESS, while Moretz in 2006 [13] reported that 91.9% of patients with headache symptoms improvement 2 years after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we felt that the radiological features warranted a surgical intervention to forestall development of any intracranial or orbital complication. Whereas failed medical therapy is treated surgically in adults with Endoscopic Sinus Surgery (ESS) [8], in children various surgical options are often initially carried out before ESS is considered mainly because of the fear of facial growth retardation that may be caused by ESS. This complication however appears largely only putative [9].…”
Section: Discussionmentioning
confidence: 99%